Preparation of future teachers of initial school is to forming of communicative competence of students - Popova, Olga; Lesik, Angelika (ScienceRise: Pedagogical Education, 2018)
An attempt to carry out the practical decision of scientific problem of preparation of future teachers to forming of communicative competence of junior schoolchildren is done in the article. Essence of concept "preparation of future teachers to forming of communicative competence of junior schoolchildren" is reasonable as the integrated system of the special knowledge, abilities and skills of communication and personality internals, that determine the general and professional level of culture of communication that will provide possibility of forming of communicative competence of junior schoolboy. The special interest at the studies of future teachers of initial school in pedagogical higher educational establishments causes problem of forming of communicative competence of junior schoolchildren. Such approach envisages the simple not transmission of knowledge and abilities from a teacher to the student, but forming for the future graduating students of readiness to the outlined type of activity. The methodical system of preparation of future teachers of initial school is suggested to form the communicative competence of students